2021
DOI: 10.1016/j.omtn.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

LOXL1 exerts oncogenesis and stimulates angiogenesis through the LOXL1-FBLN5/αvβ3 integrin/FAK-MAPK axis in ICC

Abstract: Aberrant expression of lysyl oxidase-like 1 (LOXL1) reportedly leads to fibrous diseases. Recent studies have revealed its role in cancers. In this study, we observed an elevated level of LOXL1 in the tissues and sera of patients with intrahepatic cholangiocarcinoma (ICC) compared with levels in nontumor tissues and sera of unaffected individuals. Overexpression of LOXL1 in RBE and 9810 cell lines promoted cell proliferation, colony formation, and metastasis in vivo and in vitro and induced angiogenesis. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…LOXL2 also promotes angiogenesis, since it is required for the correct assembly of collagen-IV, which is the major constituent of the basement membrane that underlies sheets of endothelial cells in blood vessels [ 63 ]. Similar effects were also associated with LOXL4 expression [ 64 ], and likewise, it is reported that LOXL1 promotes angiogenesis [ 65 ]. Interestingly, the pro-angiogenic activity of LOXL2 also does not seem to require the lysyl oxidase enzyme activity, and seems to be mediated by the LOXL2 SRCR domains [ 66 ].…”
Section: Extracellular Mechanisms By Which Lysyl Oxidases Promote Tum...supporting
confidence: 61%
See 1 more Smart Citation
“…LOXL2 also promotes angiogenesis, since it is required for the correct assembly of collagen-IV, which is the major constituent of the basement membrane that underlies sheets of endothelial cells in blood vessels [ 63 ]. Similar effects were also associated with LOXL4 expression [ 64 ], and likewise, it is reported that LOXL1 promotes angiogenesis [ 65 ]. Interestingly, the pro-angiogenic activity of LOXL2 also does not seem to require the lysyl oxidase enzyme activity, and seems to be mediated by the LOXL2 SRCR domains [ 66 ].…”
Section: Extracellular Mechanisms By Which Lysyl Oxidases Promote Tum...supporting
confidence: 61%
“…However, it fails to inhibit tumor progression in a mouse model of prostate cancer [ 130 ]. A different class of small-molecular-weight inhibitors based upon the structure of haloallylamine was recently described [ 65 ]. These early inhibitors were recently further refined, and the second generation small-molecular-weight LOXL2 inhibitors, PXS-5338, PXS-5382, and PXS-5878, were recently reported to inhibit the enzyme activity of LOXL2 more effectively that simtuzumab [ 131 ].…”
Section: Development Of Anti-tumorigenic Therapeutics Targeting Lysyl...mentioning
confidence: 99%
“…MAGEC3 also upregulates a stress-related gene, WRNIP1 [27], a DNA replication gene, MCM7 [28], and cancer-related genes, XPO5 [29] and ZSCAN16 [30]. In addition, MAGEC3 downregulates genes that are shown to induce tumor progression, including APLMR [31,32], FBLN5 [33], and FNDC1 [34,35]. Gene set enrichment analysis (GSEA) showed that MAGEC3 significantly enriched E2F targets (NES = 3.63, FDR < 0.001), G2/M checkpoint (NES = 3.20, FDR < 0.001), and DNA repair (NES = 2.28, FDR < 0.001), whereas the epithelial to mesenchymal transition was downregulated (NES = −3.34, FDR < 0.001) (Figure 3B).…”
Section: Magec3 Expression Is Associated With Stress-related Processesmentioning
confidence: 99%
“…It is overexpressed in iCCA and can be secreted outside the cell. LOXL1 protein can bind to the exposed RGD domain of FBLN5, then the complex can bind to Integrin alpha V beta 3 on the surface of vascular endothelial cells and promotes angiogenesis via the downstream FAK and MAPK signaling pathways (83). In addition, angiostatin and endostatin can also inhibit angiogenesis (84,85).…”
Section: Other Factors and Mechanismmentioning
confidence: 99%